Term planned delivery based on fetal growth assessment with or without the cerebroplacental ratio in low-risk pregnancies (RATIO37): an international, multicentre, open-label, randomised controlled trial - Rial-Crestelo, Marta; Lubusky, Marek; Parra-Cordero, Mauro; Krofta, Ladislav; Kajdy, Anna; Zohav, Eyal; Ferriols-Perez, Elena; Cruz-Martinez, Rogelio; Kacerovsky, Marian; Scazzocchio, Elena; Roubalova, Lucie; Socias, Pamela; et al. (Lancet, 2024)
BACKGROUND: The cerebroplacental ratio is associated with perinatal mortality and morbidity, but it is unknown whether routine measurement improves pregnancy outcomes. We aimed to evaluate whether the addition of cerebroplacental ratio measurement to the standard ultrasound growth assessment near term reduces perinatal mortality and severe neonatal morbidity, compared with growth assessment alone. METHODS: RATIO37 was a randomised, open-label, multicentre, pragmatic trial, conducted in low-risk pregnant women, recruited from nine hospitals over six countries. The eligibility criteria were designed to be broad; participants were required to be 18 years or older, with an ultrasound-dated confirmed singleton pregnancy in the first trimester, an alive fetus with no congenital malformations at the routine second-trimester ultrasound, an absence of adverse medical or obstetric history, and the capacity to give informed consent. Women were randomly assigned in a 1:1 ratio (block size 100) using a web-based system to either the concealed group or revealed group. In the revealed group, the cerebroplacental ratio value was known by clinicians, and if below the fifth centile, a planned delivery after 37 weeks was recommended. In the concealed group, women and clinicians were blinded to the cerebroplacental ratio value. All participants underwent ultrasound at 36 + 0 to 37 + 6 weeks of gestation with growth assessment and Doppler evaluation. In both groups, planned delivery was recommended when the estimated fetal weight was below the tenth centile. The primary outcome was perinatal mortality from 24 weeks' gestation to infant discharge. The study is registered at ClinicalTrials.gov (NCT02907242) and is now closed. FINDINGS: Between July 29, 2016, and Aug 3, 2021, we enrolled 11 214 women, of whom 9492 (84·6%) completed the trial and were eligible for analysis (4774 in the concealed group and 4718 in the revealed group). Perinatal mortality occurred in 13 (0·3%) of 4774 pregnancies in the concealed group and 13 (0·3%) of 4718 in the revealed group (OR 1·45 [95% CI 0·76-2·76]; p=0·262). Overall, severe neonatal morbidity occurred in 35 (0·73%) newborns in the concealed group and 18 (0·38%) in the revealed group (OR 0·58 [95% CI 0·40-0·83]; p=0·003). Severe neurological morbidity occurred in 13 (0·27%) newborns in the concealed group and nine (0·19%) in the revealed group (OR 0·56 [95% CI 0·25-1·24]; p=0·153). Severe non-neurological morbidity occurred in 23 (0·48%) newborns in the concealed group and nine (0·19%) in the revealed group (0·58 [95% CI 0·39-0·87]; p=0·009). Maternal adverse events were not collected. INTERPRETATION: Planned delivery at term based on ultrasound fetal growth assessment and cerebroplacental ratio at term was not followed by a reduction of perinatal mortality although significantly reduced severe neonatal morbidity compared with fetal growth assessment alone. FUNDING: La Caixa foundation, Cerebra Foundation for the Brain Injured Child, Agència per la Gestió d'Ajuts Universitaris i de Recerca, and Instituto de Salud Carlos III.
Keywords: Ultrasonography, Prenatal; novorozenec; Infant, Newborn; výsledek těhotenství; Pregnancy; Humans; Perinatal Death; perinatální smrt; Female; ultrasonografie prenatální; Pregnancy Outcome; lidé; vývoj plodu; Fetus; plod; ženské pohlaví; těhotenství; Fetal Development; Prenatal Care; prenatální péče